2000
DOI: 10.1007/s002219900261
|View full text |Cite
|
Sign up to set email alerts
|

Enslaving effects in multi-finger force production

Abstract: When a person produces isometric force with one, two, or three fingers, the other fingers of the hand also produce a certain force. Enslaving is the involuntary force production by fingers not explicitly involved in a force-production task. This study explored the enslaving effects (EE) in multi-finger tasks in which the contributions of the flexor digitorum profundus (FDP), flexor digitorum superficialis (FDS), and intrinsic muscles (INT) were manipulated. A new experimental technique was developed that allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
324
1
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 375 publications
(353 citation statements)
references
References 25 publications
25
324
1
3
Order By: Relevance
“…In an earlier study, the magnitude of enslaving has been shown to be larger for fingers adjacent to the master finger than for "remote" slave fingers (Zatsiorsky et al 2000). This similarity suggests that finger proximity is an important factor defining both slave finger magnitude and direction.…”
Section: Enslaved Finger Forcesmentioning
confidence: 87%
See 1 more Smart Citation
“…In an earlier study, the magnitude of enslaving has been shown to be larger for fingers adjacent to the master finger than for "remote" slave fingers (Zatsiorsky et al 2000). This similarity suggests that finger proximity is an important factor defining both slave finger magnitude and direction.…”
Section: Enslaved Finger Forcesmentioning
confidence: 87%
“…to explore the dependence of the direction of forces produced by fingers that are not required to produce force (enslaved forces; Li et al 1998aLi et al , 1998bZatsiorsky et al 1998Zatsiorsky et al , 2000 on the target direction; and 4. to establish whether there is a multi-finger synergy stabilizing the direction of the total force.…”
Section: To Test the Dependence Of Direction Accuracy On Target Forcementioning
confidence: 99%
“…The hypothesis assumes that the controller organizes co-variation among elemental variables to stabilize a certain value of a performance variable (F TOT or M TOT in our study). Individual finger forces co-vary in a non-task-specific fashion because of the phenomenon of enslaving, i.e., unintended force production by fingers when other fingers of the hand produce force (Li et al 1998;Zatsiorsky et al 2000). Hence, the first step was to convert the data sets from time series of finger forces to time series of elemental variables, force modes that can be, at least hypothetically, modified by the controller one at a time.…”
Section: Ucm Analysismentioning
confidence: 99%
“…In particular, unintended force production (enslaving) is the smallest in the index finger and higher in the ring and little fingers (Li et al 1998;Zatsiorsky et al 2000;Lang and Schieber 2004). Note, however, that enslaving effects were taken into account in our analysis of multifinger synergies that used not finger forces but finger modes as elemental variables.…”
Section: Rotational Efforts Into Pronation and Supinationmentioning
confidence: 99%
“…No a priori hypotheses could be formulated with respect to these comparisons. However, differences could be expected based on earlier studies that have shown effects of hand dominance on indices of finger interaction , different ability to control finger forces independently across fingers (typically, the index finger is better controlled individually as compared to the other fingers Zatsiorsky et al 1998Zatsiorsky et al , 2000, and differences in bilateral effects in symmetrical and asymmetrical two-hand tasks (Li et al 2002). Most of the cited studies used maximal force production tasks; thus one cannot readily make predictions with respect to our task of accurate sub-maximal force production.…”
Section: Introductionmentioning
confidence: 99%